2011
DOI: 10.1111/j.1476-5829.2011.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum thymidine kinase activity in canine splenic hemangiosarcoma*

Abstract: Thymidine kinase 1 (TK1) is a soluble biomarker associated with DNA synthesis. This prospective study evaluated serum TK1 activity in dogs presenting with hemoabdomen and a splenic mass. An ELISA using azidothymidine as a substrate was used to evaluate TK1 activity. Sixty-two dogs with hemoabdomen and 15 normal controls were studied. Serum TK1 activity was significantly higher in dogs with hemangiosarcoma (HSA) than in normal dogs (mean ± SEM = 17.0 ± 5.0 and 2.01 ± 0.6, respectively), but not dogs with benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
(113 reference statements)
1
28
0
Order By: Relevance
“…Another group found a contradictory function, in that mir-424 regulated VEGF and bFGF signaling by reducing expression of receptors for those cytokines and increased expression of mir-424 led to reduced proliferation and migration of endothelial cells [60]. This group also found that VEGF and bFGF had stimulatory effects on mir-424 expression, indicating that increased levels of VEGF, as seen in hemangiosarcoma, may have led to the finding of mir-424 being overexpressed, participating in a negative feedback loop [14, 60]. While it remains clear that mir-424 plays a role in angiogenesis, further studies are warranted to evaluate its specific role in canine hemangiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another group found a contradictory function, in that mir-424 regulated VEGF and bFGF signaling by reducing expression of receptors for those cytokines and increased expression of mir-424 led to reduced proliferation and migration of endothelial cells [60]. This group also found that VEGF and bFGF had stimulatory effects on mir-424 expression, indicating that increased levels of VEGF, as seen in hemangiosarcoma, may have led to the finding of mir-424 being overexpressed, participating in a negative feedback loop [14, 60]. While it remains clear that mir-424 plays a role in angiogenesis, further studies are warranted to evaluate its specific role in canine hemangiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to identify repeatable measures or other techniques that might distinguish malignant from benign masses [5, 914]. For instance, mass-to-splenic volume ratio and splenic weight as a percentage of body weight have been used to differentiate malignant from benign splenic lesions, with hemangiosarcoma masses being smaller in both categories [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5 In veterinary species, high levels of serum TK1 compared with normal range are detected in canine lymphoma, splenic hemangiosarcoma, and feline lymphoma. [2][3][4][5][6][7][8] Solid tumors in dogs and humans do not show consistently increased levels precluding serum TK1 levels as a general biomarker for all cancer histologies. 3 However, it is used in humans for breast, lung, and colorectal cancer.…”
Section: Tests For Lymphoma Veterinary Diagnostics Institute Tkcanine1mentioning
confidence: 93%
“…Elevated sTK activity has also been reported in dogs with splenic haemangiosarcoma and suggested to be due to the high proliferation rate and intimate association with the vasculature of this tumour. 17 Limitations of the current study include the variable storage conditions of samples. However, it has been shown that sTK stability is maintained despite different durations and temperatures of storage, so this was not thought to have influenced the results.…”
Section: Discussionmentioning
confidence: 99%